Colletotrichum: species, ecology and interactions - U. Damm; R. Baroncelli; L. Cai; Y. Kubo; R. O'Connell; B. Weir; K. Yoshino; P.F. Cannon (IMA Fungus)
The presentations of the Special Interest Group meeting Colletotrichum: species, ecology and interactions, held on 1 August 2010 during IMC9 in Edinburgh, UK, are outlined. Seven research projects, ranged from systematics and population genetics to host-pathogen interactions and genome projects were presented. The meeting revealed that currently major species complexes in the genus Colletotrichum are being revised and the identities of many pathogens clarified on the basis of molecular phylogenies, and that the genomes of four species are sequenced and decoded providing an enormous amount of data that are used to increase our understanding of the biology of Colletotrichum species.